Frequency of change of chlorhexidine-impregnated gel dressings for central venous catheters in critically ill patients - Mariana Ehmke Dolci; Amanda Salles Margatho; Renata Cristina de Campos Pereira Silveira (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objectives: To identify the frequency of change of chlorhexidine-impregnated gel dressings applied in central venous catheter insertion sites, describe reasons for dressing changes, and identify the amount of dressings used per adult patients admitted to an intensive care unit. Methods: Descriptive study consisting of daily record of occurrence evaluation, reason for dressing change and quantity used per patient, between April and December 2014. Descriptive statistical analysis was used. Results: A total of 159 dressings were applied at the insertion site of 64 central venous catheters whose mean frequency of dressing changes was 3.04 days. The mean number of dressing per patient was 3.1, but 83 unscheduled changes occurred before 7 days of stay, due to detachment, wetness, soiling, and loss of dressing. Conclusion: The frequency of dressing changes was less than seven days, resulting in greater quantities of dressings per patient. Detachment was the most common reason for unscheduled dressing changes.